Financial Sector Surveillance and the IMF - Gola, Carlo (IMF Working Papers; Working Paper, 2009)
The global financial crisis has magnified the role of Financial Sector Surveillance (FSS) in the Fund's activities. This paper surveys the various steps and initiatives through which the Fund has increasingly deepened its involvement in FSS. Overall, this process can be characterized by a preliminary stage and two main phases. The preliminary stage dates back to the 1980s and early 1990s, and was mainly related to the Fund's research and technical assistance activities within the process of monetary and financial deregulation embraced by several member countries. The first "official" phase of the Fund's involvement in FSS started in the aftermath of the Mexican crisis, and relates to the international call to include financial sector issues among the core areas of Fund surveillance. The second phase focuses on the objectives of bringing the coverage of financial sector issues "up to par" with the coverage of other traditional core areas of surveillance, and of integrating financial analysis into the Fund's analytical macroeconomic framework. By urging the Fund to give greater attention to its member countries' financial systems, the international community's response to the global crisis may mark the beginning of a new phase of FSS.